Assessment of Knowledge towards radiation hazards and protection protocols among medical and dental students: Assessment of radiation hazards and protection protocols among students - Fatima, Nazish; Ehsan, Shaista; Rehman, Amna; Azeem, Syeda Arzoo; Azeem, Samir (Pakistan Journal of Health Sciences, 2023)
Recently the use of radiography is growing significantly due to technology advancements and overdependence for diagnosis that’s the reason everyone is exposed to radiation and there is a linear relationship exists between radiation exposure and adverse effects on the body. Objectives: To compare the radiation hazards and protection protocols knowledge among the final year medical and dental students of private university. Methods: It was an analytical cross-sectional study conducted on final year students of Medical and Dental College of private university at Karachi Pakistan in year 2022. All students in final year MBBS and BDS irrespective of age and gender were the source population. The study populations (n=85) were those students who were randomly chosen to fill the questionnaire. The study tool in this research included a structured questionnaire. Each correct answer was scored as 1 point. Percentages and frequencies will be recorded for qualitative variables. The total knowledge scores between medical and dental students were compared using the independent t-test. Results: The data were analyzed on a total of (n=85) students. The mean ages were 22.91±0.71 and 59 (69%) were girls and 26 (31) % were boys. There were (n=45) students from the final year MBBS and (n=40) students from BDS referred as group I and II respectively. There was significant difference (t (83) = -3.052, P=0.003) in the knowledge scores group I (8.95±3.30) and group II (11.40±4.07). Conclusion: Majority of Dental students have high knowledge scores as compare to medical students